Cementation of a dual mobility cup in a well-fixed acetabular component- a reliable option in revision total hip arthroplasty? - Petri Bellova (BMC, 2021)
Abstract Background The “cup-in-cup” technique allows for revision of failed total hip arthroplasty (THA) when the cementless cup is well fixed. Furthermore, it can be used for liner wear or mechanical failure where liner replacement may be impossible or impractical. Recently, the “cup-in-cup” technique in combination with dual mobility cups (DMC) has drawn increased attention. Our aim was to report on the clinical and radiographic outcomes following this surgery. Methods From 2015 to 2020, 33 patients treated with the DMC- “cup in cup” technique were retrospectively reviewed. Fourteen patients had died while 19 were available for the final follow-up (FU), of which 15 underwent both a radiograph and a FU visit, 2 underwent a radiograph only and 2 underwent a telephone interview only. Patient-related outcome measures included the HHS and the WOMAC. Radiographs were assessed for implant loosening and positioning. Primary endpoint was revision of any cause and secondary endpoint was loosening of the DMC at the latest FU. The survival analysis was conducted using the Kaplan-Meier method. Results The mean age at surgery was 78.6 ± 7.1 (63–93) years and the mean surgery duration was 124.4 ± 52.0 (60–245) minutes. Recurrent dislocation (42.4%), periprosthetic fracture (39.4%) and polyethylene wear (6.1%) were the most frequent reasons for surgery. The mean FU duration (n = 19) was 28.5 ± 17.3 (3–64) months. The mean HHS score at FU was 59.4 ± 22.2 (29–91) and the mean WOMAC score was 59.7 ± 25.6 (15.6–93.8). Two cups were revised due to instability and one revision was performed due to periprosthetic joint infection, accounting for an overall cup survival rate of 86.8% after a mean FU of 22.9 ± 18.0 (1.5–64.6) months. The survival rate free of loosening was 90.9% after a mean FU of 22.3 ± 18.5 (1.5–64.7) months. Conclusions We found that the cementation of a DMC in a well-fixed cup is a promising short- to mid-term treatment addressing THA instability especially in elderly and frail patients, who benefit from a reduced operation time. Proper cementation technique, adequate cup positioning as well as selection of a sufficiently large DMC are crucial for treatment success. Longer FUs will be needed in the future in order to further prove the benefit of this technique.